Generation of Novel Plasmodium falciparum NF135 and NF54 Lines Expressing Fluorescent Reporter Proteins Under the Control of Strong and Constitutive Promoters - Miyazaki, Shinya; Yang, Annie S. P.; Geurten, Fiona J. A.; Marin-Mogollon, Catherin; Miyazaki, Yukiko; Imai, Takashi; Kolli, Surendra Kumar; Ramesar, Jai; Chevalley-Maurel, Severine; Salman, Ahmed M.; van Gemert, Geert-Jan A.; van Waardenburg, Youri M.; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Transgenic reporter lines of malaria parasites that express fluorescent or luminescent proteins are valuable tools for drug and vaccine screening assays as well as to interrogate parasite gene function. Different P. falciparum (Pf) reporter lines exist, however nearly all have been created in the African NF54/3D7 laboratory strain. Here we describe the generation of novel reporter lines, using CRISPR/Cas9 gene modification, both in the standard Pf NF54 background and in a recently described Cambodian P. falciparum NF135.C10 line. Sporozoites of this line show more effective hepatocyte invasion and enhanced liver merozoite development compared to Pf NF54. We first generated Pf NF54 reporter parasites to analyze two novel promoters for constitutive and high expression of mCherry-luciferase and GFP in blood and mosquito stages. The promoter sequences were selected based on available transcriptome data and are derived from two house-keeping genes, i.e. translation initiation factor SUI1, putative (sui1, PF3D7_1243600) and 40S ribosomal protein S30 (40s, PF3D7_0219200). We then generated and characterized reporter lines in the Pf NF135.C10 line which express GFP driven by the sui1 and 40s promoters as well as by the previously used ef1α promoter (GFP@ef1α, GFP@sui1, GFP@40s). The GFP@40s reporter line showed strongest GFP expression in liver stages as compared to the other two lines. The strength of reporter expression by the 40s promoter throughout the complete life cycle, including liver stages, make transgenic lines expressing reporters by the 40s promoter valuable novel tools for analyses of P. falciparum.